If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6(x + -2) = x + 5 Reorder the terms: -6(-2 + x) = x + 5 (-2 * -6 + x * -6) = x + 5 (12 + -6x) = x + 5 Reorder the terms: 12 + -6x = 5 + x Solving 12 + -6x = 5 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 12 + -6x + -1x = 5 + x + -1x Combine like terms: -6x + -1x = -7x 12 + -7x = 5 + x + -1x Combine like terms: x + -1x = 0 12 + -7x = 5 + 0 12 + -7x = 5 Add '-12' to each side of the equation. 12 + -12 + -7x = 5 + -12 Combine like terms: 12 + -12 = 0 0 + -7x = 5 + -12 -7x = 5 + -12 Combine like terms: 5 + -12 = -7 -7x = -7 Divide each side by '-7'. x = 1 Simplifying x = 1
| t*4-2=16 | | 4x^4+2x^2-20x=0 | | X+5*3x-2= | | (3-5x)/(2x-4)=0 | | 2x+3x=15findx | | 18x^2/10y^2*15y^3/24x | | 23-2=x-2+7 | | -2+2w=-4 | | 5(x+5)=7(2x-6) | | x/5-5=15 | | -x+x+5=0 | | (X+5)=7(2x-6) | | 6(3s+6)=54 | | 11m+1=8m+4 | | 6y-2=4y+14 | | 3(x+5)+5+1=31 | | -2(4x-9)=10 | | 12x-4+x=180 | | 9d^2+3d-5=0 | | 8(3m-2)=104 | | 41=6v-7 | | 42y-42y^2=20 | | (2x-1)(x+2)+(3x+1)(x-1)= | | 3(n+4)-8=11-(6-2n)52 | | 3*(2x-1)=9 | | 8x-2y=60 | | 7/(10x)=103/20 | | 4x=8x+32 | | x-0.7=5.5 | | 7x3/6 | | x*2x=50000 | | 3(2b-1)=27 |